2014
DOI: 10.1186/1471-2253-14-11
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the direction of J-tip on the placement of a subclavian catheter: real time ultrasound-guided cannulation versus landmark method, a randomized controlled trial

Abstract: BackgroundIt has been reported that the direction of the guidewire J-tip is associated with misplacement of a central venous catheter. We hypothesized that real-time ultrasound-guided infraclavicular subclavian venous cannulation would be less influenced by the direction of guidewire J-tip compared to landmark method.MethodsSixty adult patients who required subclavian venous catheterization for neurosurgery were enrolled in this prospective randomized controlled study. Patients were randomly divided into a lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 16 publications
3
15
0
1
Order By: Relevance
“…The real-time ultrasound technique has been rated as technically difficult by participating physicians [6]. As previously suggested, the benefits of the ultrasound technique may not be realized until after a significant learning period [15]. Third, we initially inserted J-tip in the cephalad direction to maximize the chance of the guidewire going up into the IJV, although this is not a good clinical practice when using landmark technique.…”
Section: Discussionmentioning
confidence: 99%
“…The real-time ultrasound technique has been rated as technically difficult by participating physicians [6]. As previously suggested, the benefits of the ultrasound technique may not be realized until after a significant learning period [15]. Third, we initially inserted J-tip in the cephalad direction to maximize the chance of the guidewire going up into the IJV, although this is not a good clinical practice when using landmark technique.…”
Section: Discussionmentioning
confidence: 99%
“…188,191,[194][195][196]199,200,[202][203][204][205] For the subclavian vein, RCTs report fewer insertion attempts with real-time ultrasound-guided venipuncture (Category A2-B evidence), 206,207 and higher overall success rates (Category A2-B evidence). [206][207][208] When compared with a landmark approach, findings are equivocal for arterial puncture 207,208 and hematoma (Category A2-E evidence). 207,208 For the femoral vein, an RCT reports a higher first-attempt success rate and fewer needle passes with real-time ultrasound-guided venipuncture compared with the landmark approach in pediatric patients (Category A3-B evidence).…”
Section: Catheter Maintenancementioning
confidence: 99%
“…[206][207][208] When compared with a landmark approach, findings are equivocal for arterial puncture 207,208 and hematoma (Category A2-E evidence). 207,208 For the femoral vein, an RCT reports a higher first-attempt success rate and fewer needle passes with real-time ultrasound-guided venipuncture compared with the landmark approach in pediatric patients (Category A3-B evidence). 209 Meta-analyses of RCTs comparing static ultrasound with a landmark approach yields equivocal evidence for improved overall success for internal jugular insertion (Category A1-E evidence), 190,202,[210][211][212] overall success irrespective of insertion site (Category A1-E evidence), 182,190,202,[210][211][212] or impact on arterial puncture rates (Category A1-E evidence).…”
Section: Catheter Maintenancementioning
confidence: 99%
“…At this point, it enters the thorax as it unites with the IJV behind the sterno-clavicular joint. 10 , 21 , 25 SCV visualization via US is possible in the clavipectoral triangle, 2–3cm distal to the point where the SCV crosses below the clavicle. As a result, US-guided SCV cannulation using an infraclavicular approach is positioned near the border of the axillary vein, which is noticeably lateral to the LM approach.…”
Section: Infraclavicular Subclavian Cannulation Under Ultrasound Guidmentioning
confidence: 99%
“… 9 , 17 Additionally, real-time longitudinal views lead to a significantly increased overall success rate, with fewer attempts, redirections, or malpositioned catheters. 10 , 16 , 25 In a prospective study by Fragou et al, 401 sedated and mechanically ventilated patients were randomized to either real-time US guidance (n=201) or LM technique (n=200) for placement of subclavian catheters by experienced operators. 10 This study found the time to obtain vascular access and number of attempts were significantly lower using real-time US guidance (p<0.05).…”
Section: Infraclavicular Subclavian Cannulation Under Ultrasound Guidmentioning
confidence: 99%